2011
DOI: 10.1007/s10493-011-9443-7
|View full text |Cite
|
Sign up to set email alerts
|

Regular dorsal dimples and damaged mites of Varroa destructor in some Iranian honey bees (Apis mellifera)

Abstract: The frequency of damaged Varroadestructor Anderson and Trueman (Mesostigmata: Varroidae) found on the bottom board of hives of the honey bee, Apis mellifera L. (Hymenoptera: Apidae) has been used as an indicator of the degree of tolerance or resistance of honey bee colonies against mites. However, it is not clear that this measure is adequate. These injuries should be separated from regular dorsal dimples that have a developmental origin. To investigate damage to Varroa mites and regular dorsal dimples, 32 hon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
2
0
2
Order By: Relevance
“…In addition, it is difÞcult to assess damage to mites (Bienefeld et al 1999, Ruttner andHänel 1992). Apparent damage may result from predatory insects (Szabo andWalker 1995, Davis et al 2007), temperature and humidity (Currie andTahmasbi 2008, Tahmasbi 2009), developmental problems (Davis 2009, Ardestani et al 2011) and storage and handling (ArechavaletaÐVelasco and GuzmanÐNovoa 2001, Vandame et al 2002). Further, Bienefeld et al (1999) suggested that young daughter mites be excluded in the assessment of grooming behavior because they have higher rates of damage (Moosbeckhofer 1992, Lodesani et al 1996 and are more likely to have "damages by chance."…”
Section: Moosbeckhofer 1992mentioning
confidence: 99%
“…In addition, it is difÞcult to assess damage to mites (Bienefeld et al 1999, Ruttner andHänel 1992). Apparent damage may result from predatory insects (Szabo andWalker 1995, Davis et al 2007), temperature and humidity (Currie andTahmasbi 2008, Tahmasbi 2009), developmental problems (Davis 2009, Ardestani et al 2011) and storage and handling (ArechavaletaÐVelasco and GuzmanÐNovoa 2001, Vandame et al 2002). Further, Bienefeld et al (1999) suggested that young daughter mites be excluded in the assessment of grooming behavior because they have higher rates of damage (Moosbeckhofer 1992, Lodesani et al 1996 and are more likely to have "damages by chance."…”
Section: Moosbeckhofer 1992mentioning
confidence: 99%
“…They referred to resistance mechanisms of honey bees as well as shorter duration of capping period in A. m. capensis compared to other races. In our previous studies, however, grooming behavior was shown to exist to a somewhat lesser extent in similar honey bee colonies of the National breeding program (Ardestani, Ebadi, & Tahmasbi, 2011.…”
Section: Discussionmentioning
confidence: 75%
“…Επιπλέον, ένα ορισμένο μέρος των ακρωτηριασμένων ακάρεων μπορεί να έχει καταστραφεί μετά από το φυσικό τους θάνατο μέσα στα σφραγισμένα κελιά του γόνου (Rosenkranz et al, 1997). Αρκετοί ερευνητές έχουν αναφέρει και ποσοτικοποιήσει τα κατεστραμμένα ακάρεα που βρίσκονται στα μελίσσια (Lodesani et al, 1996 Η συχνότητα των ομαλών ραχιαίων βαθουλωμάτων (Ardestani et al, 2011) ήταν σύμφωνη με τα αποτελέσματα του Davis (2009). Tο 1,3-3,5% των ακάρεων ήταν με δύο λακκάκια και το 3,9-6,1% με ένα, ενώ ο Davis (2009) ανέφερε ότι βρήκε 2,5% και 8,1%, αντίστοιχα .…”
Section: συμπεριφορά περιποίησηςunclassified
“…Αυτό μπορεί να οδηγήσει σε ένα ή δύο ομαλά λακκάκια στο ραχιαίο θώρακα. Είναι απίθανο οι κινήσεις των ποδιών της νύμφης (Harbo και Harris 1999b) να έχουν προκαλέσει αυτά τα ραχιαία λακκάκια (Ardestani et al, 2011).…”
Section: συμπεριφορά περιποίησηςunclassified